The role of the subthalamic nucleus in response inhibition: evidence from deep brain stimulation for Parkinson's disease. - Ray, N; Jenkinson, N; Brittain, J; Holland, P; Joint, C; Nandi, D; Bain, P; Yousif, N; Green, A; Stein, J; Aziz, T (2009)
We measured reaction times during a stop-signal task while patients with Parkinson's disease were on and off unilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN). While reaction times to a "go" stimulus improved, there was no change in reaction times to the "stop" stimulus (SSRTs). However, changes in SSRTs induced by DBS were highly dependent on baseline SSRTs (measured off stimulation), with the greatest improvements being achieved by those with particularly slow reaction times. We therefore selected only those patients whose baseline SSRTs were within the limits of a control sample (N=10). In this group, SSRTs became slower when DBS was on. This finding suggests a role for the STN in response inhibition, which can be interrupted by DBS, observable only when more general improvements in Parkinson's function are minimised. We also compared the effects of unilateral left and right sided stimulation. We found a greater increase in SSRTs after DBS of the left STN.